Oral hearing management under the E.S.C.P. regulation - Turroni, Davide (Revista Ítalo-Española de Derecho Procesal, 2022)
The ESCP is featured as a written procedure, wherein the oral hearing is granted limited space. The reason stems from the fact that oral hearing in cross-border litigations takes significantly longer time and its worth seems to be – notably in civil matters such as those included in the ESCP scope – inversely related with the case value (the smaller the value, the lesser the worth). Such a discipline gives rise to a number of significant issues, concerning its consistency with the procedural fundamental «right to be heard»; the correlative margin of discretion the court may rely on in deciding whether a hearing shall be scheduled or not; not least the role played by the modern communication technologies in this respect. The Author deals with such issues in their multiple features and connections, trying thence to offer proper answers thereto. The overall Author’s view is that the ESCP Regulation’s restrictive approach to oral hearing is reconciliable with the right to be heard and that the broad discretion conferred to the court in this respect is justified as well.